The Metabolic Syndrome and Risk of Chronic Kidney Disease: Pathophysiology and Intervention Strategies. (22nd February 2012) - LaGuardia, Heather A.; Hamm, L. Lee; Chen, Jing
Abstract : Metabolic syndrome is characterized by a clustering of cardiovascular risk factors, including abdominal obesity, elevated blood pressure and glucose concentrations, and dyslipidemia. The presence of this clinical entity is becoming more pervasive throughout the globe as the prevalence of obesity increases worldwide. Moreover, there is increased recognition of the complications and mortality related to this syndrome. This paper looks to examine the link between metabolic syndrome and the development of chronic kidney disease.